2018
DOI: 10.1080/09273948.2018.1424343
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Development of Rhegmatogenous Retinal Detachment in Patients with Uveitis

Abstract: Prevalence of RRD in uveitis was 7% and development of RRD was encountered in posterior and panuveitis. Infectious uveitis (specifically ARN) formed a high risk for RRD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…Although other investigators have reported that cicatrizing conjunctivitis is associated with an increased risk of RD after KPro implantation, we did not find such an association. 24–26 Similar to a report by Chak et al, we did not find an association between the performance of a YAG laser membranotomy for a RPM and an increased risk of RD, as reported by Jardeleza et al 24,27 However, our findings that postoperative aphakia and idiopathic vitritis were associated with an increased risk of RD are consistent with those of Jardeleza et al 24…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Although other investigators have reported that cicatrizing conjunctivitis is associated with an increased risk of RD after KPro implantation, we did not find such an association. 24–26 Similar to a report by Chak et al, we did not find an association between the performance of a YAG laser membranotomy for a RPM and an increased risk of RD, as reported by Jardeleza et al 24,27 However, our findings that postoperative aphakia and idiopathic vitritis were associated with an increased risk of RD are consistent with those of Jardeleza et al 24…”
Section: Discussionsupporting
confidence: 91%
“…Although other investigators have reported that cicatrizing conjunctivitis is associated with an increased risk of RD after KPro implantation, we did not find such an association. [24][25][26] Similar to a report by Chak et al, we did not find an association between the performance of a YAG laser membranotomy for a RPM and an increased risk of RD, as reported by Jardeleza et al 24,27 However, our findings that postoperative aphakia and idiopathic vitritis were associated with an increased risk of RD are consistent with those of Jardeleza et al Our center has previously reported on the safety of concurrent KPro and tube shunt implantation and demonstrated that the incidence of sight-threatening postoperative complications was not increased in eyes in which a tube shunt was implanted with the KPro compared with eyes in which a tube shunt was not. 6 Although our prior study was not sufficiently powered to detect differences between these two groups for each postoperative complication, the 6.5% of eyes that developed a RD in the group that underwent concurrent KPro and tube shunt implantation was approximately half of the 12.1% that developed a RD in the group in which a tube was not implanted.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…21 Vitreous inflammation can lead to posterior vitreous detachment with subsequent retinal breaks, and idiopathic vitritis is a reported risk factor for RD after KPro. 4,21,22 Idiopathic vitritis occurred frequently in our series, but detailed risk factor analysis was not performed because of the small cohort size and is reported elsewhere. 4 It has also been shown that a chronic low grade of inflammation from the KPro device itself can promote a strong inflammatory response within the retina, leading to an aggressive PVR response following RD.…”
Section: Discussionmentioning
confidence: 99%
“…ARN has the highest rate of RRD of any uveitis. 17 The reported rate of RRD in ARN varies widely from 20% to 73%. 4,6,[8][9][10][18][19][20][21][22][23][24][25] This wide range likely results from differences in ARN severity, time to treatment, treatment plan, and length of follow-up.…”
Section: Retinal Detachment Rates and Associated Factorsmentioning
confidence: 99%